Analisis Inovasi Kurikulum Merdeka Berdiferensiasi pada Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah Umum - Nurlaili, Nurlaili; Suranda, Novalyo; Purwanto, Purwanto (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This research aims to determine the innovation of an independent, differentiated curriculum in Islamic religious education learning. This research uses a type of library research. The research results show that differentiated learning is a method or effort made by teachers to meet students' needs and expectations. Differentiated learning is an effort to adapt the learning process in the classroom to meet the individual learning needs of each student. Implementation of a differentiation-based independent curriculum in Islamic Religious Education learning in Public Schools (Elementary, Middle School, High School and College) includes: (1) Content differentiation, when teachers know several aspects of students' needs through mapping, educators can provide content different, to each student according to learning needs and profiles such as grouping students with learning styles in the form of audio, visual, audio visual and kinetic (motion), (2) Process Differentiation, in this learning process educators need to understand the learning needs of students/ students whether they are able to study independently, in groups, or require special treatment (special assistance) to understand the concept of the material by grouping students according to the students' readiness, abilities and interests and learning talents. (3) Product Differentiation. The products produced can be projects, presentations, designs, speeches, memorization, and religious practices. (4) Environmental differentiation, can use classroom facilities, outdoor (park), computer laboratory and prayer room. Abstrak Penelitian ini bertujuan untuk mengetahui inovasi kurikulum merdeka berdiferensiasi dalam pembelajaran Pendidikan agama Islam, penelitian ini menggunakan jenis penelitian kepustakaan (library research). Hasil penelitian menunjukkan bahwa pembelajaran berdiferensiasi adalah cara atau upaya yang dilakukan guru untuk memenuhi kebutuhan dan harapan murid. Pembelajaran berdiferensiasi sebagai usaha untuk menyesuaikan proses pembelajaran di kelas untuk memenuhi kebutuhan belajar individu setiap siswa. Implementasi kurikulum merdeka berbasis diferensiasi pada pembelajaran Pendidikan Agama Islam di Sekolah Umum (SD, SMP, SMA, dan Perguruan Tinggi) meliputi: (1) Diferensiasi konten Pada saat guru telah mengetahui beberapa aspek kebutuhan peserta didik melalui pemetaan, maka pendidik dapat memberikan konten yang berbeda, kepada setiap peserta didik sesuai dengan kebutuhan dan profil belajar seperti pengelompokan peserta didik dengan gaya belajar berupa audio, visual, audio visual dan kinetik (gerak), (2) Diferensiasi Proses, Proses pembelajaran ini pendidik perlu memahami kebutuhan belajar peserta didik/mahasiswa apakah mereka mampu belajar secara mandiri, kelompok, atau membutuhkan perlakuan khusus (pendampingan khusus) untuk memahami konsep materi dengan mengelompokkan peserta didik sesuai pada kesiapan, kemampuan dan minat dan bakat belajar peserta didik. (3) Diferensiasi Produk, Produk yang dihasilkan dapat berupa projek, presentasi, desain, pidato, hafalan, dan praktek ibadah. (4) Diferensiasi Lingkungan dapat menggunakan fasilitas kelas, outdoor (taman), laboratorium komputer, dan Musholah.